The role and place of music in Dipo Ceremony amongst the Krobo people of Ghana: A cultural exploration - Djokpe, Michael Kwame (Research Journal in Advanced Humanities, 2020)
Dipo, like all puberty or initiation rites, is an initiation ceremony performed for young girls who are of puberty age among the people of Krobo in the Eastern Region of Ghana. The Dipo rite ushers girls of puberty age into womanhood. It is one important event, during which they perform different types of indigenous music. At such cultural event, Ghanaian indigenous music is consummately performed in its context playing vital roles in the ceremony. A Guide for the Preparation of Primary School African Music Teaching Manual (1999); propounds that “songs are like books in a culture that is based upon oral traditions. They are means of transmitting culture and knowledge…” (P.16). In Krobo custom, the women in the community provide music during the entire ceremony. According to Nyumuah (1998), the millet beer (ngmada) is prepared on Friday. In the midst of the brewing, the women dance around the fireplace to the tune of klama songs.